The Effect of Variance Return, Market Value, and Dividend Payout Ratio on Holding Period of Shares (Case Study at the Companies included in LQ-45 Index Year 2012-2018) - Irni Yunita; Marwa Dewi Ahdiyati Salim; Hendratno Hendratno (Jurnal Manajemen Indonesia, 2020)
The purpose of this research is to investigate the effect of variance return, market value, and Dividend Payout Ratio (DPR) on holding period of shares of the companies listed in LQ-45 Index period 2012-2018. The population of the study were the companies listed in LQ-45 Index period 2012-2018. The sampling technique used in the study was purposive sampling. Using the technique, 26 companies were obtained. The analysis method used was panel data regression analysis. The result of study showed that variance return, market value, and Dividend Payout Ratio (DPR) simultaneously had significant effect on holding period of shares. Partially, variance return had significant negative effect on holding period of shares. Market value and Dividend Payout Ratio (DPR) had positive and significant effect on holding period of shares. Based on the result of study, investors who would like invest could pay attention to the risks they would have. If investors intended to maintain their shares in long term, they would need to invest in companies that had low risks. The risks were reflected by the value of variance return. In addition, if investors intend to maintain their shares for a long term, they will need to make investment in a company that has a bigger size. The company size is reflected from the value of market value. Then, if investors intend to maintain their shares for a long term, they will need to make investment in a company that give a large dividend. So, investors will get more profits from the companies. Keywords—variance return; market value; Dividend Payout Ratio (DPR); holding period